Marketing Opportunities for Bank Syariah Mandiri e-Banking Services as a Payment Method - Muhammad Mansyur (Research Horizon, 2021)
In the development of technology in this era of globalization, various industrial fields have begun to crawl to utilize and develop services based on technology and the internet. Likewise, the financial industry such as banking also competes with each other to provide internet-based services or it is known that the term e-Banking. At this stage of service in Indonesia in particular very rapidly. Moreover, now people must also be able to accept various other services such as internet-based buying and selling (e-commerce), electronic money (e-Money), and internet-based banking services (e-Banking). From various forms of activity that have turned to technology and the internet, there are also market opportunities for the Islamic finance industry. By taking advantage of payment opportunities, Islamic banks must be able to take advantage of market opportunities that exist in the community, and overall improve the ability of the Islamic financial system in the face of rapid technological developments so that they can provide Islamic-based services but can also provide services needed by the community such as e-Banking.